Aleisyan Almadaniu Fi Alshryet Walqanun - Salih , Zilal (Islamic Sciences Journal, 2023)
ABSTRACT We all know that civil disobedience is one of the peaceful protest methods that people resort to to confront the ruling authority in their country on grounds of injustice, lack of justice and widespread corruption, with which the citizen seeks to lift the injustice against him. Civil disobedience is a general act, meaning overt popular behavior, and it is considered a weapon of the oppressed to resist tyranny, by declaring rebellion against some laws, such as striking at work and schools, and avoiding the use of violence, which is thus different from criminal disobedience. The first is a collective message represented by raising slogans, holding inquiring programmes and media presence, in order to achieve the desired goals.